Risk attitude, beliefs, and information in a corruption game: An experimental analysis - Siegfried K. Berninghaus; Sven Haller; Tyll Krüger; Thomas Neumann; Stephan Schosser; Bodo Vogt (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2010)
For our experiment on corruption we designed a coordination game to model the influence of risk attitudes, beliefs, and information on behavioral choices and determined the equilibria. We observed that the participants' risk attitudes failed to explain their choices between corrupt and non-corrupt behavior. Instead, beliefs appeared to be a better predictor of whether or not they would opt for the corrupt alternative. Furthermore, varying the quantity of information available to players (modeled by changing the degree of uncertainty) provided additional insight into the players' propensity to engage in corrupt behavior. The experimental results show that a higher degree of uncertainty in the informational setting reduces corruption.
urn:nbn:de:swb:90-197750
Keywords: D73; K42; C91; C92; 330; Corruption; game theory; experiment; risk attitude; beliefs; Korruption; Spieltheorie; Risikopräferenz; Informationsverhalten; Erwartungstheorie; Test